Enhancing Scientific Heritage Access Through AI-Powered Assistants and Collaboration Platforms in Academic Ecosystems - Georgieva, Evgeniya; Georgiev, Tsvetozar; Stefanova, Tsvetelina (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This study investigates how artificial intelligence and collaboration platforms enhance scientific heritage access within academic ecosystems. Within the context of evolving infrastructures for scientific discovery and heritage preservation, the analysis examines advanced digitization methods, semantic networks, autonomous research agents, and mainstream database AI integrations. Findings indicate that while these technologies democratize knowledge, institutions must proactively address inherent ethical, legal, and cybersecurity vulnerabilities.
Keywords: Digital Scientific Heritage; Artificial Intelligence; AI-Powered Research Assistants; Academic Ecosystems; Knowledge Graphs; Decentralized Science